New Progress in Basic Research of Macrophages in the Pathogenesis and Treatment of Low Back Pain - Yan, Miaoheng; Song, Zongmian; Kou, Hongwei; Shang, Guowei; Shang, Chunfeng; Chen, Xiangrong; Ji, Yanhui; Bao, Deming; Cheng, Tian; Li, Jinfeng; Lv, Xiao; Liu, Hongjian; et al. (Frontiers in Cell and Developmental Biology, 2022)
Low back pain (LBP) is quite common in clinical practice, which can lead to long-term bed rest or even disability. It is a worldwide health problem remains to be solved. LBP can be induced or exacerbated by abnormal structure and function of spinal tissue such as intervertebral disc (IVD), dorsal root ganglion (DRG) and muscle, among them IVD degeneration is considered as the most important pathogenic factor of LBP. Inflammation, mechanical load, immune response, hypoxia etc., can result in LBP by affecting the spinal tissue, among which inflammation and immune response is the key link. Inflammation and immune response play a double-edged sword role in LBP. As the main phagocytic cells in the body, macrophages are closely related to body homeostasis and various diseases. Recent studies have shown that macrophages are the only inflammatory cells that can penetrate into the closed nucleus pulposus, they are expressed in various structures of the IVD, and the number is positively correlated with the degree of IVD degeneration. Moreover, macrophages can play a phagocytosis role or regulate the metabolism of DRG and muscle tissues through neuro-immune mechanism, while the imbalance of macrophages polarization will lead to more inflammatory factors to chemotaxis and aggregation, forming an "inflammatory waterfall" effect similar to positive feedback, which greatly aggravates LBP. Regulation of macrophage migration and polarization, inhibition of inflammation and continuous activation of immune response by molecular biological technology can markedly improve the inflammatory microenvironment, and thus effectively prevent and treat LBP. Studies on macrophages and LBP were mainly focused in the last 3-5 years, and they are becoming star molecules attracting more and more scholars' attention. This paper summarizes the new research progress of macrophages in the pathogenesis and treatment of LBP, to provide an important reference for effective clinical prevention and treatment.